Comparative assessment of topical steroids, topical tretenoin (0.05%) and dithranol paste in alopecia areata - Das Sudip; Ghorami R; Chatterjee T; Banerjee Gautam (Wolters Kluwer Medknow Publications, 2010)
Background: There have been various controversial reports regarding the efficacy of topical agents in topical therapy of alopecia areata. Aim: The study aims to find out the effective ones among the readily available ones for a dermatologist. Materials and Methods: Eighty patients were chosen from the skin OPD of Bankura Sammilani Medical College, Bankura, West Bengal, after evaluating the exclusion criterions. Treatments were continued for 3 month period and a follow up after further 3 months. After dividing them into four groups-group-I (topical steroids), group-II (topical tretinoin 0.05%) group-III (dithranol paste 0.25%), and group-IV (white soft petrolatum jelly)-patients were evaluated. Results: Seventy percent of group-I, 55% of group-II, 35% of group-III, and 20% of the control group (white soft petrolatum jelly) responded favorably. Side effects in the form of dermatitis and hyperpigmentation were seen in group-III. However, no patient discontinued from the study. Conclusion: We conclude that both topical steroids and tretinoin were fairly effective in limited variant of alopecia areata.